(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: Infantile colic is defined as excessive crying for more than three hours a day at least three days a week for one week or more in an otherwise healthy baby. It is most frequently observed in neonates and infants aged two weeks to four months. Objective: To assess the incidence of infantile colic and effectiveness of conventional therapy. Materials and Methods: This was a prospective cross sectional study of 50 cases carried out in Paediatric out patient department in Combined Military Hospital (CMH) Ghatail during the period of September 2010 to August 2012. Data recorded including demographics, clinical presentations, management and the outcome of therapy. Results: Out of the total 50 patients, 24(48%) were male and 26(52%) were female. Male:Female=1:1.08. Babies delivered vaginally suffered more 32(64%), full term delevered babies 33 (66%) suffered more than that of gestational age group <37 wk. Non-exclusive Breastfed (Formula fed, combination of breastfed and formula fed) babies having more incidence of colic 31(62%). Maximum patients 26(52%) had history of cry 4-5 hours per day. Motion (Rocking, bouncing, walking etc) 18(36%), change of diet 14(28%) were considerable satisfactory treatments. Conclusion: Since it is a self limiting condition, conventional therapy should be tried for instant relief. Journal of Armed Forces Medical College Bangladesh Vol.12(1) 2016: 83-87